Complete response in a critically ill patient with ALK-negative anaplastic large cell lymphoma treated with single agent brentuximab-vedotin. Issue 3 (3rd March 2016) - Oregel, Karlos Z.; Everett, Emily; Zhang, Xinhai; Nagaraj, Gayathri
ABSTRACT: Anaplastic large cell lymphoma (ALCL) is a rare hematological malignancy and a distinct subtype of mature T-cell lymphomas. ALCL is comprised of two clinically distinct but morphologically similar sub-class under 2008 WHO classification: cutaneous and systemic. Primary systemic ALCL is further sub-categorized into tumors that carry the anaplastic lymphoma kinase (ALK) gene rearrangement or not; ALK- positive versus ALK-negative disease respectively. Traditionally, both forms of primary systemic ALCL have been treated upfront with an anthracycline based combination chemotherapy such as CHOP. More recently an antibody drug conjugate, brentuximab-vedotin (BV), directed against CD30 antigen has shown promise in CD30 expressing hematologic malignancies such as Hodgkin's lymphoma and ALCL. At the present time, this novel antibody-drug conjugate has been approved in the treatment of patients with ALCL after failure of at least one prior multi-agent chemotherapy regimen in the United States. We present a case describing a previously healthy 48 year-old female diagnosed with ALK-negative ALCL who achieved complete response with upfront single agent brentuximab-vedotin. It is the first case described in the literature utilizing BV in the first line setting particularly in a patient with multi-organ failure and critically ill at time of diagnosis. This case highlights the full potential that targeted therapies can exert over hematological malignancies while also minimizing treatment related toxicities. Abbreviations : AE: adverse event; ALCL: anaplastic large cell lymphoma; ALK: anaplastic lymphoma kinase; ASCT: autologous stem cell transplant; BEAM: BCNU/carmustine, etoposide, ara-C, and melphalan; BV: brentuximab vedotin; CHEOP: cyclophosphamide, daunorubicin, vincristine, prednisone, etoposide; CHOP: cyclophosphamide, doxorubicin, vincristine, prednisone; CR:complete response; G3+: grade 3 or higher; MTD: maximum tolerated dose; ORR: overall response rate; OS: overall survival; PFS: progression-free survival.